Environmental scanning of electric vehicle technologies - Panaga, Juvie Talaue (University of the Philippines Diliman, 2017)
Environmental scanning of electric vehicle (EV) technologies will showcase the current situation of electric vehicles in the Philippines specifically ETrikes and EJeepney. Its existing policies, programs and incentives and other related information. Further it will look into the Global EV Outlook 2016 by the Organisation for Economic Co-operation and Development / International Energy Agency (OECD/IEA). And it will recommend policies and programs for the national government can implement to hasten EV uptake in the public transport.